Do imaginário angolano - Oliveira, Américo Correia de (Africana Studia, 2020)
This is a study on the cycle of ogros in the traditional Angolan narrative ( 118 narratives), printed in Portuguese, comprising the majority of the Angolan ethno-linguistic communities. Every agro denomination, in the severa! bantu Angolan languages, - kixí, this one common to the majority, kazumbi, tshingandagari, tshiphupu, kalelwa, kúiu, mjumbi a nkenge, mihange, tchazangombe, ndongo- that belong to this corpus of traditional narratives, has as a common semanteme, the "spirit of the ancestor", holder, by merit, of the power good and e vil, which the living need to attract (engolimento/"re-ligião") and I or exorcize ( desventramento/distanciação). Contrary to what many famous africanists might say, our destiny seems to belong, somewhere, to the God(s) ... in Angola, to the ancestors.